The influence of teaching practice of ideological and political integration into sports on students’ mental health - Peng Zhou (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This research is conducted to determine the impact of ideological and political integration on students' mental health. The mental health of college students has always been a concern for society. The prevalence of psychological disorders among college students is approximately 25 percent, increasing, which is cause for concern. This study employs questionnaires and statistical analysis to examine the effects of psychological and political factors on physical education teaching for the mental health of college students. With a recovery rate of 94.2%, 198 out of 210 randomized questionnaires were positive. The results of Guttmann's inquiry are adopted, and its repeatability reliability is 0.81, which has some validation in terms of validity and validity criteria. The spherical test result indicates a level of significance of 0.000, indicating a level of significance. Strengthening the training system, the practice of athletics, and the difficulty of communication in college and university-integrated teaching management determines its irreplaceable function and influence in promoting college students' mental health.